PENGARUH IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH NOMOR 12 TAHUN 2009 TENTANG KAWASAN TANPA ROKOK OLEH SATUAN POLISI PAMONG PRAJA TERHADAP PENEGAKAN DISIPLIN MASYARAKAT DI KAWASAN UMUM KOTA BOGOR - Daman Huri; Denny Hernawan; G. Goris Seran (LPPM Universitas Djuanda Bogor, 2019)
The aim of the research is to analyze the effect of policy implementation of Local Regulation No. 12/2009 concerning Areas Without Cigarettes by Civil Service Police Unit on the enforcement of public discipline in the public areas of Bogor City. The policy implementation is understood in Edward III’s perspective based on four aspects, namely communication, resource, disposition/attitude, and bureaucratic structure. The public discipline uses Elizabeth Hunrlock’s perspective based on three aspects, namely rule/norm, consistence, punishment and reward. The research uses Weight Mean Score formula to count the mean and to describe it. It also uses Spearman Rank Correlation formula based on SPSS version.20 to test a hypothesis concerning the relation of policy implementation to public discipline. The results of the research indicate that the policy implementation gets the mean score 3.28, meaning good enough, and the public discipline gets the mean score 3.65, meaning good. The coefficient correlation of two variables gets value 0.406, categorized as the middle. By t-test, the research gets tcount value 3.688 and ttable (N=71) value 1.666. Therefore, tcount > ttable means that alternative hypothesis is accepted. The coefficient determination indicates 16.4% of contribution of policy implementation to public discipline.Keywords: Areas Without Cigarettes, Policy Implementation, Public Areas, Public Discipline.